2010
DOI: 10.1638/2009-0258.1
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biochemistry Values, Plasma Mineral Levels, and Whole Blood Heavy Metal Measurements in Wild Northern Goshawks (Accipiter gentilis)

Abstract: Serum chemistry panels and complete mineral and heavy metal screens were performed on blood samples from eight adult northern goshawks (Accipiter gentilis) breeding in Pennsylvania. Serum chemistry panels were performed to determine the health status of each bird. Biochemical values measured included serum glucose, sodium, potassium, chloride, magnesium, uric acid, creatine kinase, and aspartate transaminase. Glucose, creatine kinase, and aspartate transaminase values were elevated when compared with published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
5
12
2
Order By: Relevance
“…Metal ion determination. Biliary and blood metals were measured using a PerkinElmer Elan 6100 ICP-MS System (inductively coupled plasma MS system) at the Pennsylvania Animal Diagnostic Laboratory System (PADLS), New Bolton Center Toxicology Laboratory of the University of Pennsylvania School of Veterinary Medicine, as previously described (52). For each bile sample, bile from 2 animals was combined, and weight and volume were recorded before measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Metal ion determination. Biliary and blood metals were measured using a PerkinElmer Elan 6100 ICP-MS System (inductively coupled plasma MS system) at the Pennsylvania Animal Diagnostic Laboratory System (PADLS), New Bolton Center Toxicology Laboratory of the University of Pennsylvania School of Veterinary Medicine, as previously described (52). For each bile sample, bile from 2 animals was combined, and weight and volume were recorded before measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of e.g., canvasback ducks (Aythya valisineria) and blackcrowned night heron (Nycticorax nycticorax), laboratory rats and humans have shown that ALAT and ALKP plasma levels increase with exposure to various groups of organochlorines and PBDEs (Alonso et al, 2010;Champoux et al, 2002;Dieter, 1974Dieter, , 1975Dieter et al, 1976Dieter et al, , 1977Dieter and Wiemeyer, 1978;Fischbein, 1985;Hayes et al, 1984;Kutlu et al, 2007). These perturbations have shown to be a function of species, exposure route, duration and compound (Arnold et al, 1993;Chu et al, 1994;Stout et al, 2010). Our findings indicate that OHC exposure may have an impact on hepatocyte integrity and function.…”
Section: Relationships Between Ohcs and Bccpsmentioning
confidence: 96%
“…Zn measurements. To measure Zn, mouse embryonic hearts were homogenized in 100 μl PBS (Ca 2+ /Mg 2+ free) and Zn was measured by inductively coupled plasma mass spectrometry (ICP-MS) using an Elan 6100 (PerkinElmer) at the PADLS New Bolton Center Toxicology Laboratory, School of Veterinary Medicine of the University of Pennsylvania, as was previously described (32). Briefly, after the weight and volume of E14.5 hearts were measured, the sample was digested overnight with twice the amount (weight/volume) of 70% nitric acid at 70°C and 0.15 ml of the digested sample was diluted with deionized water to a final volume of 5 ml for analysis.…”
Section: Author Contributionsmentioning
confidence: 99%